Plant-Based Antioxidant Peptides: Impact on Oxidative Stress and Gut Microbiota - Lee, Chi-Ching; Fan, Hongbing; Tsopmo, Apollinaire; Regenstein, Joe M.; Ashaolu, Tolulope Joshua; Lee, Chı-Chıng (Taylor & Francis, 2025)
Plant-based peptides can be obtained from natural and climate-friendly sources. these peptides show various bioactivities including antioxidant activity. Oxidative stress has an impact on the gut microbiota causing inflammation, insulin resistance, osteoporosis, cancer, and several chronic diseases like type 2 diabetes, arthritis, hypertension, and atherosclerosis. therefore, antioxidant peptides may significantly affect oxidative stress as a potential alternative to conventional medication. the production of antioxidant peptides from plant-based protein sources through conventional and innovative approaches may provide promising strategies to improve gut microbiota. Recent studies in plant-based antioxidant peptides (PBAP) focus on their advanced identification and characterization techniques, structure-activity relationship, improvement of extraction and purification, cellular and molecular mechanisms, specific health applications in preventing and managing conditions with gut microbiota, and commercial applications in nutraceuticals. Short-chain fatty acids and reactive sulfur species are specific gut-derived metabolites that can improve metabolic function by modulating oxidative stress and the immune system. this review highlights the influence of food oxidants on the gut microbiota and PBAP-induced modulation of gut microbiota. Moreover, the production of PBAP and the challenges in their application will be discussed.
Keywords: Plant-based food peptides; Antioxidant peptides; Oxidative stress; Antioxidants; Gut microbiota